Synthesis and optical and electrochemical properties of water-soluble cationic fluorophores based on bispyridinium and dibenzothiophene-S, S-dioxide. (25th January 2017) - Chen, Guiting; He, Ruifeng; Yang, Wei; Zhang, Bin
Abstract : Two water-soluble cationic fluorophores (FSOPyCl andFSOmiCl ) based on bispyridinium and dibenzothiophene- S, S -dioxide show deep blue emission, and exhibit high photoluminescence quantum yields of 69% and 50% in water, respectively. Abstract : Two novel water-soluble π-conjugated small molecules based on dibenzothiophene- S, S -dioxide and bispyridinium salts, namedFSOPyCl andFSOmiCl, were successfully synthesized. Both molecules showed deep blue light emission, with photoluminescence peaks at about 408 and 405 nm in aqueous solution, respectively. Their photoluminescence quantum yields (PLQYs) in aqueous solution were as high as 68.9% and 50.3%, respectively. Electrochemical measurements suggested that they have excellent electron affinity, with lowest unoccupied molecular orbital (LUMO) energy levels at −3.78 and −3.94 eV, respectively. Due to their unique properties including large planarity, good thermal stability, excellent electron affinity and high fluorescence efficiency, FSOPyCl andFSOmiCl may be promising construction units for preparing water/alcohol-soluble conjugated materials with good optoelectronic performance.